Indonesian Local Government’s Accountability and Performance: The Isomorphism Institutional Perspective - Muhammad Ahyaruddin; Rusdi Akbar (Journal of Accounting and Investment, 2018)
This research aims to explore the accountability and performance of government agency in perspective of institutional theory. It analytically answer two research questions: Do institutional isomorphism exist in the implementation of performance measurement system and accountability in public sector organizations? (RQ1) and Do government agencies actually use performance measurement information to aid decision-making and help plan for future performance improvement? (RQ2). This study is a qualitative research to answer two research question proposed with use semi-stuctured and open interview from SKPD officers in the local government of Yogyakarta Province. The results of interview were analyzed use thematic content analysis. Our finding show that three form of institutional isomorphism (coersive, mimetic and normative) were existed in the implementation of performance measurement system and accountability in public sector organizations. This result also show an interesting finding in government agency that performance information who reported in LAKIP was only a formality. The information content in LAKIP is not used as feedback to aid decision-making and plan for future performance improvement.